Effects of exogenous melatonin on sleep quality and menopausal symptoms in menopausal women: a systematic review and meta-analysis of randomized controlled trials. Issue 6 (June 2021) - Yi, Mingyu; Wang, Sixue; Wu, Ting; Zhang, Xinyue; Jiang, Li; Fang, Xiaoling
Abstract: Importance: Because of the bothersome symptoms during women's menopausal period and the severe side effects of hormone therapy, it is meaningful to find new breakthroughs in improving menopausal women's quality of life. Objective: We performed a systematic review and meta-analysis of randomized controlled trials (RCTs) evaluating melatonin intake on the improvement of sleep quality, general menopausal symptom, mood states, as well as interaction of estradiol levels and body mass index (BMI) in menopausal women. Evidence Review: We used the search terms "melatonin" together with "menopause" or "post-menopause" or "peri-menopause" in multiple databases online including PubMed, Web of Science, Embase, Clinical trial, Cochrane Library, and China National Knowledge Infrastructure from the first publication year to October 2020. Interesting data included characteristics of the study design, study participants, intervention, and outcome measures. Risk of biases in RCTs was evaluated with the Cochrane tool. Fixed-effect models and random-effect models were used for meta-analysis according to heterogeneity. Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed in our study. Findings: Eight cohorts ( n = 812) evaluating the effects of melatonin in menopausal women were included. Melatonin was used in every study with differences existing in dose (1 mg - 5 mg) and duration (3 to 12 mo). Improved physical symptoms (standard mean difference [SMD] −0.376; 95% CI, −0.599 to −0.153, P = 0.001) merged in four RCTs. Melatonin treatment resulted in no benefits to sleep quality (SMD −0.659; 95% CI, −1.535 to 0.217, P = 0.141) and general menopause symptoms (SMD −0.625; 95% CI, −1.354 to 0.105, P = 0.093) in four and three RCTs, respectively. More specifically, melatonin did not solve the psychological (SMD −0.026; 95% CI, −0.372 to 0.321, P = 0.884, I 2 = 70.3%), sexual (SMD −0.661; 95% CI, −1.416 to 0.093, P = 0.086) and vasomotor (SMD −0.256; 95% CI, −0.701 to 0.188, P = 0.258) issues. No significant changes were observed in anxiety (SMD 0.018; 95% CI, −0.519 to 0.556, P = 0.946), depression (SMD 0.133; 95% CI, −0.435 to 0.702, P = 0.646), BMI (weighted mean difference 0.029 kg/m 2 ; 95% CI, −0.183 to 0.240, P = 0.790) or estradiol levels (weighted mean difference 0.016 pg/mL; 95% CI, −1.220 to 1.252, P = 0.980). Conclusions: Melatonin seems to improve physical symptoms in menopausal women, but the general menopausal symptoms, sleep quality, mood state, estradiol levels, and BMI did not improve under melatonin intervention. However, multiple large-scale clinical randomized trials are needed to validate our conclusions. Abstract : Supplemental Digital Content is available in the text